Wavelet based Video Compression Using Various Encoding Techniques: A Relative Study - Nithin.s.s, Mr.; L.Padma, Dr.; N.Subash, Suresh (International Journal of Engineering and Technology, 2018)
In this paper, we are functioning to execute various coding based methods with empirical wavelet transform (EWT) for video compression. These methods are Video coding using wavelet and H.264, Video coding using wavelet and SPIHT, Video coding using wavelet and combination of H.264 and SPIHT, Video coding using wavelet and combination of Huffman and SPIHT, Video coding using wavelet and LZW and ourÂ proposed method Video coding wavelet and BWT, MTF and Huffman. For our implementing purpose, we are using MATLAB 2014. By using this evaluation we can check the performance of different techniques. Here we quantify PSNR and compression ratio of these various methods. Using these results, we can compare the performance of these various methods. The proposed method output shows that it got better results than previous methods. Â Â Â